NurOwn, phase 2, randomized, clinical trial in patients with ALS: Safety, clinical, and biomarker results. (10th December 2019) - Berry, James D.; Cudkowicz, Merit E.; Windebank, Anthony J.; Staff, Nathan P.; Owegi, Margaret; Nicholson, Katherine; McKenna-Yasek, Diane; Levy, Yossef S.; Abramov, Natalie; Kaspi, Haggai; Mehra, Munish; Aricha, Revital; et al.
Abstract : Objective: To determine the safety and efficacy of mesenchymal stem cell (MSC)-neurotrophic factor (NTF) cells (NurOwn®, autologous bone marrow-derived MSCs, induced to secrete NTFs) delivered by combined intrathecal and intramuscular administration to participants with amyotrophic lateral sclerosis (ALS) in a phase 2 randomized controlled trial. Methods: The study enrolled 48 participants randomized 3:1 (treatment: placebo). After a 3-month pretransplant period, participants received 1 dose of MSC-NTF cells (n = 36) or placebo (n = 12) and were followed for 6 months. CSF was collected before and 2 weeks after transplantation. Results: The study met its primary safety endpoint. The rate of disease progression (Revised ALS Functional Rating Scale [ALSFRS-R] slope change) in the overall study population was similar in treated and placebo participants. In a prespecified rapid progressor subgroup (n = 21), rate of disease progression was improved at early time points ( p < 0.05). To address heterogeneity, a responder analysis showed that a higher proportion of treated participants experienced ≥1.5 points/month ALSFRS-R slope improvement compared to placebo at all time points, and was significant in rapid progressors at 4 and 12 weeks ( p = 0.004 and 0.046, respectively). CSF neurotrophic factors increased and CSF inflammatory biomarkers decreased in treated participants ( p < 0.05) post-transplantation. CSF monocyte chemoattractant protein-1 levels correlated with ALSFRS-R slope improvement up to 24 weeks ( p < 0.05). Conclusion: A single-dose transplantation of MSC-NTF cells is safe and demonstrated early promising signs of efficacy. This establishes a clear path forward for a multidose randomized clinical trial of intrathecal autologous MSC-NTF cell transplantation in ALS. Classification of evidence: This phase II study provides Class I evidence.